Shear Stress Regulates TRPV4 Channel Clustering and Translocation from Adherens Junctions to the Basal Membrane. Issue 1 (December 2017) - Baratchi, Sara; Knoerzer, Markus; Khoshmanesh, Khashayar; Mitchell, Arnan; McIntyre, Peter
Abstract Localized Ca2+ influx via TRPV4 on the surface of endothelial cells greatly influences endothelial adaptation to blood flow, but how mechanical stress from blood flow controls TRPV4 integration into this physiological function is not fully understood. Here, we studied the spatial organization of TRPV4 and its relationship to the adherens junction component β-catenin using single- and dual-color direct stochastic optical reconstruction microscopy (dSTORM). In non-stimulated endothelial cells, TRPV4 is clustered in small protein islands, as is β-catenin. Using dual-color imaging, we found that TRPV4 and β-catenin reside in similar islands and can be found at both the basolateral and basal membranes. Following shear stress stimulation, TRPV4 molecules formed smaller clusters, with the majority residing outside of clusters. Further shear stress stimulation changed the molecular distribution of TRPV4 molecules, limiting them to the basal membrane. This redistribution and the smaller clusters resulted in the segregation of TRPV4 from β-catenin. Furthermore, TRPV4 trafficking was controlled by focal adhesion kinase and activation of the α5ß1 integrin. These highly differentiated spatial redistributions suggest that mechanotransduction of blood flow is controlled via a more complex hierarchy than previously thought.